Marketing Strategies: own brands as a competitive differential in the supermarket market - Souza, Tereza de; Queiroz, Tatiana Silva de; Campos, Domingos Fernandes; Vieira, Ricardo Sergio Gomes (Review of Business Management, 2009)
The objective of this work is to study marketing strategies and customer’s perception in relation to the own-brand offered by the supermarket sector. The research had an exploratory and descriptive feature. In the exploratory phase the managers of three great networks of supermarkets were interviewed; in the descriptive phase 240 customers were interviewed by using a structured gathering tool, originally compounded by closed questions, directed to the apprehension of data about their behavior according to the purchases of own-brand products. By using the Chi-square method, it was statistically verified a dependence between the marketing strategies used in supermarkets and the socio-economical and individual profile of the clients. The research results have identified a framework of customer perceptions regarding the frequency and reasons for purchase, differences in price and quality for brand leaders, and other variables to determine the definition of a successful marketing strategy. Key words: Retail. Own- brand. Consumer's behavior.